Economic Sociology - Past and Present, with a View to the Future - Korsnes, Olav (Sociologija. Mintis ir veiksmas, 1999)
The article aims to discuss the "New Economic Sociology" by developing a comparative analysis of two sociological approaches: the New Economic Sociology and the Societal Approach. The author takes his departure in a historical overview of the development of the New Economic Sociology, central to which are the ideas of Mark Granovetter and Rose whose critique of the Societal Approach is similar to Granovetter's programme. The author suggests that it is best to understand the difference between the two appraoches as a discussion over the principles of the sociological theory and develops his analysis by questioning the possible concequences that the approaches may have both politically and for the practice of empirical research.
Keywords: economic sociology; Mark Granovetter; Michael Rose; societal approach